Application of advanced communication and control technologies for smart grid : a comprehensive review - Surender Reddy, S (International Journal of Engineering and Technology, 2018)
This paper presents a comprehensive review of advanced control and communication technologies of smart grid (SG). Various func-tions/features of SG include real-time pricing, voltage/VAr control, frequency control, power quality, demand response management, distri-bution system restoration, and reconfiguration, distributed generation dispatch and storage. There is a strong requirement to control these functions, as well as to communicate within themselves. Suppose, if two-way communication is not possible then it cannot be considered as a function of SG. When trying to track or monitor a function, one must be able to control, command, and communicate with it. In order to control observation ability and measure of some type of numerical quantity that is obtained from a real time measuring device being moni-tored is necessary. Some of these measurable quantities are: overvoltage limits, security measures and contingency analysis. This paper addresses various challenges of control and communication techniques of SG.Â Â